Thrust tectonics in the Andean retro-foreland basin of northern Peru: Permian inheritances and petroleum implications. (April 2017) - Calderon, Ysabel; Baby, Patrice; Hurtado, Christian; Brusset, Stéphane
Abstract: In northern Peru, the Huallaga-Moyabamba-Marañon Subandean foreland basin system results from the interaction between thin and thick-skinned tectonics. Geophysical data and the construction of two balanced cross-sections show that this structural configuration has been controlled by Permian inheritances. A fossilized west-verging Middle Permian fold and thrust belt, which developed during the Gondwanide orogeny, has been partly reactivated by the Andean compression and controlled thick-skinned tectonics propagation. This west-verging thrust system is still active and causes the crustal and damaging seismicity of the Moyabamba region. Late Permian salt, which has sealed the Middle Permian fold and thrust belt, controlled thin-skinned tectonics propagation and the development of the must large overthrust of the Peruvian Subandean zone. The fossilized and partly reactivated Middle Permian fold and thrust belt constitutes a new petroleum play for the exploration in the northern Peruvian Subandean basins. Sub-thrust traps of the Moyabamba and Huallaga wedge-top basins are particularly attractive but stay unexplored. Highlights: Andean retroforeland of northern Peru is deformed by east-verging thin-skinned and west-verging thick-skinned tectonics. West-verging thick-skinned tectonics results from the reactivation of a Middle Permian fold and thrust belt. Post-orogenic Late Permian salt distribution controlled large thin-skinned tectonics propagation. Crustal and damaging seismic activity is due to the reactivation of the west-verging Middle Permian thrusts. The fossilized and reactivated Middle Permian fold and thrust belt constitutes a new petroleum play for the exploration.